The Development of Worksheets IPA with Cognitive Conflict Strategy to Reduce Misconception in Heat Material - Heny Ekawati Haryono; Nisaul Barokati Selirowangi; Khafidoh Nurul Aini (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This study aims to analyze the feasibility of LKS IPA with cognitive conflictstrategy, that has been developed to reduce misconceptions Heat material. This researchincludes the development of research which refers to the 4-D models by Thiagarajan. TheSamples are50 students of SMP Negeri 1 Lamongan. The design of the study is one grouppretest-posttest design implemented in a single group without a comparison group. Researchinstrumenst used in the form of validation sheets, observation sheets, and diagnostic testsmisconceptions. The misconceptions identification can be done by individuals or groups usingCertain of Response Index (CRI). Techniques to determine the improvement of learningoutcomes in this study using techniques normalized gain <g>. Data analysis is the initialdiagnostic test (pretest) aims to identify the concepts that experienced student misconceptions,while the end of the diagnostic test (posttest) aims to determine the effectiveness of IPA LKScognitive conflict strategy in overcoming misconceptions. The result shows the degression ofmisconceptions. The decline of students misconceptions after study shows that thedevelopment of LKS IPA with cognitive conflict strategy provides a good contribution inreducing students misconceptions. Based on the understanding of the concept of positivestudent learning outcomes indicate that happens to change, the use of LKS IPA with cognitiveconflict strategy contributes improve students' conceptions in line with the findings.